1996
DOI: 10.1105/tpc.8.12.2309
|View full text |Cite
|
Sign up to set email alerts
|

Pathogen-induced systemic activation of a plant defensin gene in Arabidopsis follows a salicylic acid-independent pathway.

Abstract: A 5-kD plant defensin was purified from Arabidopsis leaves challenged with the fungus Alternaria brassicicola and shown to possess antifungal properties i n vitro. The corresponding plant defensin gene was induced after treatment of leaves with methyl jasmonate or ethylene but not with salicylic acid or 2,6-dichloroisonicotinic acid. When challenged with A. brassicicola, the levels of the plant defensin protein and mRNA rose both in inoculated leaves and in nontreated leaves of inoculated plants (systemic leav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

32
693
7
12

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 844 publications
(744 citation statements)
references
References 63 publications
(86 reference statements)
32
693
7
12
Order By: Relevance
“…One of the Arabidopsis target genes, At-ATG5, has already been demonstrated to participate in plant defense against B. cinerea. 24 In addition, we confirmed that 3 additional Arabidopsis genes, At-WRKY7, At-FEI2, and At-PMR6, are involved in the plant defense responses against B. cinerea.…”
Section: Discussionsupporting
confidence: 64%
“…One of the Arabidopsis target genes, At-ATG5, has already been demonstrated to participate in plant defense against B. cinerea. 24 In addition, we confirmed that 3 additional Arabidopsis genes, At-WRKY7, At-FEI2, and At-PMR6, are involved in the plant defense responses against B. cinerea.…”
Section: Discussionsupporting
confidence: 64%
“…Perturbations in SA-dependent signaling have been reported to affect jasmonic acid (JA)-dependent signaling, including the expression of PDF1.2 (Clarke et al, 1998;Dewdney et al, 2000;Gupta et al, 2000;Penninckx et al, 1996;Penninckx et al, 1998;Rao et al, 2000). We found enormous genotype-speci®c variation in PDF1.2 mRNA levels ( Figure 6c).…”
Section: Analysis Of Defense Gene Expression In Double Mutantsmentioning
confidence: 99%
“…JA-and ethylene-mediated signaling pathways are distinct from the classic SA-mediated SAR pathways [15]. For example, induced systemic resistance (ISR), which is triggered by nonpathogenic root-colonizing bacteria, is JA and ethylene dependent [16,17] and is independent of SA and PR-gene activation [18,19]. The JA response mutant jar1 and the ethylene response mutant etr1 lose ISR upon treatment with Pseudomonas fluorescens WCS417r, but remain normal level of pathogen-induced SAR [20,21], indicating that JA and ethylene responses are critical for the ISR-signaling pathway [22,23].…”
Section: Introductionmentioning
confidence: 99%